(4R*,4aR*,7aS*)-5-Oxo-6-phenyl-4a,5,6,7,7a,8-hexahydro-4H-furo[2,3-f]isoindole-4-carboxylic acid - Horak, Yuriy I. (International Union of Crystallography, 2013)
The asymmetric unit of the title compound, C(17)H(15)NO(4), contains two independent molecules with similar geometric parameters. In both molecules, the conformation of the cyclohexene ring is half-chair, while the pyrrolidinone ring adopts an envelope conformation with the γ-carbon atom of the α-pyrrolidinone ring as the flap. In the crystal, O—H⋯O hydrogen bonds between the carboxylic and carbonyl groups link alternate independent molecules into chains propagating in the b-axis direction. The crystal packing also features weak C—H⋯π interactions.